2009
DOI: 10.1111/j.1365-313x.2009.03797.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genes in the ASYMMETRIC LEAVES2/LATERAL ORGAN BOUNDARIES (AS2/LOB) family in Arabidopsis thaliana, and functional and molecular comparisons between AS2 and other family members

Abstract: The ASYMMETRIC LEAVES2 (AS2) gene is required for the generation of the flat and symmetrical shape of the leaf lamina in Arabidopsis. AS2 encodes a plant-specific protein with an AS2/LATERAL ORGAN BOUNDARIES (AS2/LOB) domain that includes a cysteine repeat, a conserved single glycine residue and a leucine-zipper-like sequence in its amino-terminal half. The Arabidopsis genome contains 42 genes, including AS2, that encode proteins with an AS2/LOB domain in their amino-terminal halves, and these genes constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
138
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(155 citation statements)
references
References 30 publications
3
138
0
1
Order By: Relevance
“…Five other LBD genes display similar or root-specific expression patterns like LBD20, with two of these, LBD14 and LBD33, the closest phylogenetically related to LBD20 (Shuai et al, 2002;Matsumura et al, 2009). This suggests subgroups of LBD proteins may have unique roles in roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five other LBD genes display similar or root-specific expression patterns like LBD20, with two of these, LBD14 and LBD33, the closest phylogenetically related to LBD20 (Shuai et al, 2002;Matsumura et al, 2009). This suggests subgroups of LBD proteins may have unique roles in roots.…”
Section: Discussionmentioning
confidence: 99%
“…This domain also determines the unique role of each LBD protein with LOB domains from other members unable to functionally replace each other (Matsumura et al, 2009;Majer and Hochholdinger, 2011). The LOB domain contains a Cys repeat (C motif), a conserved Gly residue, and a Leuzipper-like motif.…”
Section: Discussionmentioning
confidence: 99%
“…expressed in young lateral roots and LBD29 in lateral root primordia, while LBD18 was more ubiquitously detected in most organs [19,28,34]. To investigate the temporal and spatial expression of LBD genes during callus induction, we chose LBD16 and LBD18 as the representatives and carefully examined their expression patterns during callus induction using ProLBD16:GUS and ProLBD18:EGFP:GUS transgenic seedlings.…”
Section: Lbd16 Lbd17 Lbd18 and Lbd29 Are Dramatically And Rapidly Imentioning
confidence: 99%
“…The results of misexpression experiments indicate that during postembryonic development, JLO function is required for the initiation of plant lateral organs. A recent study showed that the LOB domain of AS2 cannot be functionally replaced by those of other members of the LOB family, indicating that dissimilar amino acid residues in the LOB domains are important for characteristic functions of the family members (Matsumura et al, 2009). …”
mentioning
confidence: 99%